Comparison of new Biomarkers in the Diagnosis of Perinatal Asphyxia - Boskabadi, Hassan; Zakerihamidi, Maryam; Ghayour-Mobarhan, Majid; Bagheri, Fatemeh; Moradi, Ali; beiraghi toosi, mehran (Iranian Journal of Child Neurology, 2023)
Objectives Precise and early diagnosis of neonatal asphyxia may improve its outcomes. New studies aim to identify diagnostic biomarkers in neonates at risk for brain damage. The current study was designed to evaluate the diagnostic value of new biomarkers neonatal asphyxia. Materials & Methods This prospective study was conducted with an available sampling of infants upper 35 weeks of gestational age, including neonates with asphyxia (case group) and healthy controls, 2014-2022, in Ghaem Hospital, Mashhad, Iran. Data collection was performed utilizing a researcher-made questionnaire, including maternal and neonatal characteristics, as well as clinical and laboratory evaluation. Serum umbilical cord levels of interleukin-6 (IL6), interleukin-1-beta (IL- 1β), pro-oxidant-antioxidant balance (PAB), and heat shock protein-70 (HSP70), as well as nucleated red blood cells count (NRBC), were determined. Data were analyzed by t-test, Chi-square, receiver operating characteristic (ROC), and regression models. Results Variables interleukin-6(IL6) (P<0.0001), IL1β (P<0.0001), PAB (P<0.0001), NRBC/100WBC (P<0.0001) and HSP70 (P<0.0001) in the two groups, the difference was statistically significant. In the diagnosis of asphyxia, the most sensitive marker (89%) was IL1β more than 2.39 pg/ml and HSP 70 upper than 0.23 ng/ml while IL6 higher than 9pg/ml determined as the most specific marker (85%). For the diagnosis of asphyxia, combination of HSP + PAB and IL6 + lL1b + PAB + NRBC/100WBC possesses the prediction power of 93.2% and 87.3% respectively. Conclusion According to data analysis, the combination of new biochemical markers (NRBC count, IL6, IL1β, PAB, HSP 70) could be a reliable marker for the diagnosis of infants with asphyxia. The composition of the HSP + PAB indicators is more valid predictions 93.2% compared to the other combined indicators for the diagnosis of asphyxiated neonates. PAB values correlate with the severity of asphyxia.